Caracterización morfométrica y percepción sociocultural de la extracción de palmeras utilizadas en fiestas carnavaleras en Iquitos, 2025 - Fernandez Gomez, Bruno Andres (2025)
The extraction of palm trees for carnival festivities represents a traditional practice with significant environmental implications in the Peruvian Amazon. This study aimed to characterize morphometrically and socioculturally the extraction of palm trees used in carnival festivities in Iquitos during 2025. A descriptive cross-sectional design was employed, evaluating 73 extracted palm specimens and surveying 33 vendors and 73 buyers through non-probabilistic convenience sampling. Results revealed that extraction concentrates mainly on two species: Huasaí (Euterpe precatoria) with 50.7% and Cashapona (Socratea exorrhiza) with 45.2% of specimens. Morphometric analysis showed an average diameter of 11.93 cm, height of 9.24 m, and 26.95 leaves per palm, indicating preference for young individuals. 97.3% of palms presented good phytosanitary condition, while 20.5% had reproductive structures, evidencing direct impact on reproductive capacity. Vendors, with diverse experience (30.3% with over 6 years), obtain palms mainly from own lands (72.7%) using manual methods (81.8%). Perception of resource availability is divided: 45.5% perceive decline versus 48.5% who consider stability. Buyers (43.8% annual, 79.5% buy one palm) prioritize price (56.2%) as selection criteria, with 67.1% abandoning palms on public roads post-carnival. Both groups show high receptivity toward sustainable practices (94.0% vendors, 65.7% buyers) and acceptance of regulation (75.7% and 71.2% respectively). It is concluded that there exists a consolidated market dynamic with potential to implement sustainable management strategies, requiring stakeholder articulation to develop alternatives that preserve cultural tradition while minimizing environmental impact.